Five-finger hypnosis alleviates fatigue in chronic kidney patients - Ida Rochani; Rizka Yunita; Alwin Widhiyanto (KHD-Production, 2025)
Fatigue is a common symptom experienced by chronic kidney failure patients undergoing hemodialysis, which significantly affects their quality of life. This study aims to evaluate the effect of five-finger hypnosis therapy on reducing fatigue in chronic kidney failure patients in the hemodialysis room of Bhayangkara Lumajang Hospital. The research design used was pre-experiment with pre-and post-test approaches. The population in this study were chronic kidney failure patients undergoing regular hemodialysis, with a total of 40 patients. The sample consisted of 36 respondents selected through the purposive sampling technique. Data were collected using the Fatigue Assessment Scale (FAS) questionnaire to measure fatigue levels and the five-finger hypnosis module for intervention techniques. Data were analyzed bivariate using the paired sample t-test. The results showed that the average value of the fatigue level before the five-finger hypnosis intervention was 31.83, with a standard deviation of 4.98. After the intervention, the respondents' average fatigue level was 25.27, with a standard deviation of 4.53. Data analysis using the Paired Sample T-Test showed a significant effect between five-finger hypnosis therapy on reducing fatigue levels with a value of ρ = 0.000 (ρ <0.05). Five-finger hypnosis therapy can be integrated as part of a non-pharmacological care program to improve the quality of life of patients in hemodialysis units.